Program Design of a Color Spectrum Detection Device - Assoc. Prof., Shuhratjon Xidirov; Master's student, Ahrorbek Sobirjonov (Genius Journals, 2022)
The article presents the technology of creating a new modern seed sorting device for efficient use of agricultural machinery
Keywords: aerodynamic sorter; dielectric sorter; spectrum